2009
DOI: 10.1161/strokeaha.109.548545
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Lacunes and Microvascular Lesions on Poststroke Depression

Abstract: The cumulative vascular burden resulting from chronic accumulation of lacunar infarcts within the thalamus, basal ganglia, and deep white matter may be more important than single infarcts in the prediction of PSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 54 publications
6
62
0
Order By: Relevance
“…Six studies reported on a combination of people with and without dementia described as a single group. Two studies assessed patients with stroke (Esiri et al, 1997;Santos et al, 2009), one study elderly without describing their cognitive status (Longstreth et al, 2009). Three papers concerned patients with cerebral amyloid angiopathy (CAA) (Olichney et al, 1997;Soontornniyomkij et al, 2010;De Reuck et al, 2011a).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies reported on a combination of people with and without dementia described as a single group. Two studies assessed patients with stroke (Esiri et al, 1997;Santos et al, 2009), one study elderly without describing their cognitive status (Longstreth et al, 2009). Three papers concerned patients with cerebral amyloid angiopathy (CAA) (Olichney et al, 1997;Soontornniyomkij et al, 2010;De Reuck et al, 2011a).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 2000) was used most frequently, followed by the Cognitive Assessment Screening Instrument (Teng et al, 1994). Four studies based their diagnosis on a combination of neuropathology (cerebrovascular disease, AD, stroke, CAA) and clinical examination (dementia, depression) (Lee et al, 2000;Ballard et al, 2000;Santos et al, 2009;Soontornniyomkij et al, 2010) ( Table 1). …”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A recent autopsy study suggested that lacunar infarcts may predict PSD. 13 There is a lack of large-scale studies on PSD in lacunar stroke. The aim of this study was to determine the relationship between CMB and PSD in lacunar stroke survivors.…”
mentioning
confidence: 99%